A study in cultured neuronal networks - Bayat, Fazıl Kemal. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2021., 2021)
In this study, two platforms, combining multi-electrode arrays and optogenetic methods, were developed to study living neural networks in vitro. Both platforms, which included stimulation of neural networks developed in culture and monitoring of their activities, were tested using primary neuronal cultures obtained from mice and their operability and usability were demonstrated. In the rst platform, dorsal root ganglion cells were made to emit uorescent light when calcium in ux occurs by optoge netic technique. In this platform stimulation was provided electrically through multiple electrode arrays and experiments were performed under uorescent microscopy. The evoked activity was monitored through calcium transitions and the analyzed results re vealed the network connections. Next, the network connections determined by analysis were con rmed by immunostaining that showed connections physically. The results obtained illustrated that the dorsal root ganglion nerve cells could establish connec tions with each other to form networks. In the second platform, hippocampal cells were used and neurons were made excitable with light using the optogenetic approach. After that, the optical stimulation using a digital micro mirror device for excitation was performed locally and focused. Spontaneous and stimulated extracellular elec trical activity was monitored and recorded with multiple electrode arrays. On this platform, bilateral and closed-loop electrophysiology applications were performed and multi-channel and experiment examples were presented. The results show that the new platform designed for extracellular electrophysiology applications, with the option of multi-channel, artifact-free and closed-loop experimentation, eliminates the de ciencies and problems of those proposed in the previous studies. In conclusion, in the presented study, it has been shown that multi-electrode arrays can be successfully integrated with optogenetic methods that have both activity monitoring and stimulation purposes.
Keywords: Neural networks (Neurobiology); Cell culture.; Electrodes.